Dedicated small bowel follow-through - experience of Clinical institute of radiology in Ljubljana - Koprivnik, Mateja (Radiology and oncology (Ljubljana), 2003)
Background. Small bowell is a difficult part of the alimentary tract to examine. Radiologic modality most commonly used has been the conventional small bowel follow-through (SBFT), which has often been done in a cursory manner, without fluoroscopy and manual palpation. The purpose of our study is to present dedicated SBFT and to assess its sensibility and specificity. Patients and methods. We analysed 35 dedicated SBFT, performed from April to September 2002, in patients. Findings were evaluated according to clinical follow-up, endoscopy and surgery. Results. Our findings were consistent with clinical follow-up, endoscopy and surgery in 33 patients. In 2 patients our findings were false negative. Our results show 89.5% sensitivity and 100% specifity. Conclusions. An adequate per-oral examination remains the most reliable toll for diagnostic evaluation of the small bowel.
Keywords: Barijev sulfat; Barium Sulfate; Celiac Disease; Celiakija; Contrast Media; Crohn Disease; Crohnova bolezen; črevesje; Črevesne bolezni; Črevo tanko; Diagnosis; diagnostika; Dispepsija; Duodenitis; Dyspepsia; Fluoroscopy; Fluoroskopija; Intestinal Diseases; Intestine, Small; Kontrastna sredstva; Radiography; radiološka diagnostika